2022
DOI: 10.1021/acsabm.2c00549
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework (UiO-66)-Based Temperature-Responsive Pesticide Delivery System for Controlled Release and Enhanced Insecticidal Performance against Spodoptera frugiperda

Abstract: Spodoptera frugiperda is a global pest that brings about great disasters to crops. Conventional pesticide formulations often suffer from poor water solubility, low stability, burst release, weak leaf adhesion, and low efficiency. To improve the insecticidal activity of pesticides, a stimuli-responsive controlled release pesticide delivery system (PDS) has attracted extensive attention in recent years. This paper reports a temperatureresponsive controlled release PDS based on poly(N-isopropyl acrylamide) (PNIPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Enhancing the adhesion of pesticides on foliage can effectively improve pesticide utilization. Based on the potential adhesion and prominent viscoelasticity of JNSs-stabilized Pickering emulsions presented in rheological measurement, an adhesive pesticide emulsion is prepared by loading the model pesticide Av (termed Av-Emul). Along the route reported in our previous work, the adhesion ability of the Av-Emul is evaluated by comparing the amounts of samples remaining on interfaces before and after simulating rainwash.…”
Section: Resultsmentioning
confidence: 99%
“…Enhancing the adhesion of pesticides on foliage can effectively improve pesticide utilization. Based on the potential adhesion and prominent viscoelasticity of JNSs-stabilized Pickering emulsions presented in rheological measurement, an adhesive pesticide emulsion is prepared by loading the model pesticide Av (termed Av-Emul). Along the route reported in our previous work, the adhesion ability of the Av-Emul is evaluated by comparing the amounts of samples remaining on interfaces before and after simulating rainwash.…”
Section: Resultsmentioning
confidence: 99%
“…The biosafety of the nanopesticide was studied according to the previous literature. The germination rate of maize seeds and the growth times of maize seedlings were used to simply evaluate the phytotoxicity of the nanopesticide. ,, The experiment steps were similar to the previous literature, and the nanopesticide sample was MXene-TA-β-CYF.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, nanomaterial-based pesticide delivery systems (PDSs) have drawn increasing interest for their controllable preparation route, improved water dispersion stability, high pesticide loading rate, sustained release, and enhanced insecticidal activity. Materials including carbon nanomaterials, polymers, metal–organic frameworks, mesoporous materials, etc., are developed as nanocarriers for pesticide delivery in the past decade. , Especially, the stimuli-responsive controlled release of PDSs has attracted extensive interest because the pesticide release behavior can be accurately controlled according to exogenous stimuli, which will greatly improve the utilization and activity of pesticides. For example, Kaziem et al developed a carboxymethyl starch-modified hollow mesoporous silica-based PDS for abamectin delivery and found that the release of abamectin can be controlled by pH and enzyme dual stimuli . Song and colleagues reported a carboxymethyl chitosan surface-decorated carbon nanoparticle for emamectin benzoate (EB) delivery and found that it exhibited pH-responsive release performance .…”
Section: Introductionmentioning
confidence: 99%
“…For another instance, Shen, Wu, Song, and co-workers developed a temperature-responsive nanocomposite, namely, IDC@UiO-66-(COOH) 2 -PNIPAm, to release pesticide and efficiently control Spodoptera frugiperda . UiO-66-(COOH) 2 composed of Zr 4+ and pyromellitic acid (H 4 BTEC) linkers was used as a reservoir to load insoluble indoxacarb (IDC), a broad-spectrum insecticide, with a high loading capacity of 78.69%, followed by the modification of a temperature-sensitive poly­( N -isopropylacrylamide) (PNIPAm) by a covalent grafting approach to develop IDC@UiO-66-(COOH) 2 -PNIPAm.…”
Section: Mof-based Nanoplatforms For Crop Protectionmentioning
confidence: 99%
“…119 Carboxymethyl cellulose (CMC), a pH-responsive polymer molecule, was modified on the surface of UiO-66-NH 2 by an amidation For another instance, Shen, Wu, Song, and co-workers developed a temperature-responsive nanocomposite, namely, IDC@UiO-66-(COOH) 2 -PNIPAm, to release pesticide and efficiently control Spodoptera f rugiperda. 120 UiO-66-(COOH) 2 composed of Zr 4+ and pyromellitic acid (H 4 BTEC) linkers was used as a reservoir to load insoluble indoxacarb (IDC), a broad-spectrum insecticide, with a high loading capacity of 78.69%, followed by the modification of a temperaturesensitive poly(N-isopropylacrylamide) (PNIPAm) by a co-valent grafting approach to develop IDC@UiO-66-(COOH) 2 -PNIPAm. IDC@UiO-66-(COOH) 2 -PNIPAm showed a temperature-dependent release behavior due to PNIPAm molecular chain shrinking above 32 °C enabling IDC molecules to be extruded and released.…”
Section: Journal Of Agricultural Andmentioning
confidence: 99%